Investigation of stresses on a flat plate with a hole using experimental techniques and comparing the results using algor finite element programme / Zulkifi Sharudin, Shahrul Nizar Md. Salleh and Suriyati Supono - Sharudin, Zulkifi; Md. Salleh, Shahrul Nizar; Supono, Suriyati (Faculty of Mechanical Engineering, Universiti Teknologi MARA, 1997)
The aim of our project is making a research about the characteristic of stress which existed at a flat plat with a tensile force applied to the plats. The flat plat used in our project here was bored in a circular and elliptical hole, so that we could determined the effect of stress concentration factor through the values of stress we’ve got. This research was done by using sketches in all process with 2 techniques: a) Experimental Techniques b) Algor FEA programme 1997. After all the values we needed from both techniques determined, the next method was comparing all the results of stresses from both methods. From all the results in the comparison between algor and experiment techniques done, conclusion and all the comments were explained in the report. The main objective of this research: 1. Determined the uses of Algor FEA in engineering design. 2. The uses of Algor FEA in doing certain project, such as save times and energy in designing and also comparing the methods nowadays.